2018
DOI: 10.21037/jtd.2018.01.47
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and surgical factors affecting the switch from minimally invasive transthoracic occlusion to open surgery during ventricular septal defect repair

Abstract: Among all the anatomic classifications, membranous aneurysm VSD had the highest risk for switching from minimally invasive transthoracic closure to surgical repair under CPB. During the early period, the surgeons were not yet skilled with the minimally invasive transthoracic closure procedure, and the main causes of switching to surgical repair under CPB were that the delivery system could not pass through the ventricular septal defect and significant residual shunts persisted after releasing the occluder. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…Compared with those in previous literature, 12 the proportion of occlusion device shedding or shifting, which are the most common cause of procedure failure, was higher in this study cohort. The rate of VSD closure failure varies because of different VSD locations.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Compared with those in previous literature, 12 the proportion of occlusion device shedding or shifting, which are the most common cause of procedure failure, was higher in this study cohort. The rate of VSD closure failure varies because of different VSD locations.…”
Section: Discussioncontrasting
confidence: 86%
“…In this study, 522 children underwent minimally invasive surgical VSD closure, and 19 cases (3.64%) of failure occurred. The failure rate was low compared with that in other studies 3–5 8–12. In the 5 years from 2015 to 2019, the annual failure rate was similar and not significantly different likely due to our team having substantial experience in surgical VSD closure in children.…”
Section: Discussionmentioning
confidence: 47%
“…If closure cannot be achieved or any complication occur, a rapid transition to open-heart surgery is possible [ 2 , 3 , 5 , 7 , 8 , 11 - 13 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al [ 3 ] analyzed the factors for switching to conventional repair. In their series, residual shunts (8/340; 2.4%) and valvular insufficiency (5/340; 1.5%) were the main factors.…”
Section: Discussionmentioning
confidence: 99%
“…This study comprised patients 3 months to 33 years old and weighing 3.5 to 61 kg (mean 14.3 § 6.51 kg). 14 Review of these data indicates that perventricular repair is an early and evolving technology that presents promise as proposed in this issue by Wang et al in a well-trained multidisciplinary setting. 4 Importantly, Wang et al found that the periventricular ventricular septal defect closure technique was well tolerated and associated with fast-track extubation, earlier discharge from the intensive care unit, and earlier hospital discharge compared with the conventional surgical technique with cardiopulmonary bypass.…”
mentioning
confidence: 99%